The Consequence of Firm Policies on Human Capital Accounting in Kenya - Lio, San (International Journal of Accounting and Financial Reporting, 2023)
The purpose of this paper was to evaluate the moderating consequence of firm policies on Human Capital (HC) accounting implications among large and medium size listed firms in Kenya. The moderating power of firm policies can provide a good source of knowledge on whether Kenyan firms are able to account for their HC as material investments to be leveraged for improved firm market value. Using explanatory-mixed method cross-sectional survey, the study was conducted on a target population 165 Kenyan Chief Finance Officers (CFOs), from whom primary data was gathered by the use of questionnaire with both closed-ended and open-ended questions. The study variables were measured using both the ordinal scale and Likert-type of scale. The Partial correlation analysis, multiple linear regression analysis, and statistical tests such as the F-test and ANOVA were used. Multiple regression analysis was used to determine the moderating effect of firm policies on HC accounting frameworks such as: (i)the Human Resource Accounting (HRA) theory acceptability, (ii) financial measures considered in HRA accounting adoption, (iii) tenability of the existing HRA tools, (iv) usage of existing HRA tools, and (v) essessability of existing HRA tools. According to the study findings, the model was found to significantly predict ACC for HC Adoption as indicated by an F-value of 26.642 and a significant p-value of < 0.001. Accordingly, company policies would facilitate ACC for HC adoption in Kenyan medium and large organizations. On the other hand, the independent variables were found to explain 14.8% of the variation in ACC for HC adoption in Kenyan medium and large organizations without policies as the moderating variable. This implied that HRA discipline acceptability and positive impact of ACC for HC on firm value would enable Kenyan medium and large organizations to successfully adopt ACC for HC so long as ACC for HC tools’ are tenable, applicable, assessable for efficacy, had requisite ACC for HC metrics, and key constituents in organizations were aware of the tools. However, the independent variables were found to explain 29.7% of the variation in ACC for HC adoption with policies as the moderating variable. This implied that company policies were a moderating variable of the frameworks for HC accounting adoption in Kenyan medium and large organizations, and more than doubled their predictive power on the dependent variable by 14.9%. In conclusion, firm policies were a profound ingredient in promoting HC ACC adoption to leverage the treatment of HC as material investments for improved firm market value in Kenya. This study recommended that Kenyan firms needed to focus more on robust firm policies if they hoped to achieve their HC ACC goals.